2004
DOI: 10.1155/2004/686913
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breathing and Skin Stimulation Techniques on Labour Pain Perception of Turkish Women

Abstract: OBJECTIVE: To determine the effect of breathing techniques and nurse-administered massage on the pain perception of pregnant woman during labour. SETTING AND PARTICIPANTS: The present study was conducted among pregnant women (75% primiparous) admitted to the SSK Bakirkoy Women and Children's Hospital (Istanbul, Turkey) between January 1, and September 1, 2000. The patients were in their 38th to 42nd week of pregnancy, not at high risk and expected to have normal vaginal delivery. They were selected from volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 18 publications
(19 reference statements)
3
35
0
6
Order By: Relevance
“…Current evidence on endogenous pain modulatory pathways that are activated by repeated massage for painful stimuli suggests that the analgesic effects of massage need to be studied using animal models (Uvnas-Moberg et al, 1993;Lund, 2000;Lund et al, 2002). The majority of recent trials on massage for labour and other forms of pain have been designed to test the effects of structured programmes of massage used in combination with other techniques (Field et al, 1997;Chang et al, 2002;Yildirim and Sahin, 2004;Ezzo, 2007). To improve the quality of evidence on massage interventions combined with relaxation techniques for labour and birth pain, our key task is to follow recent recommendations, to correct design flaws and methodological weakness in existing trials (Smith et al, 2006;Ezzo, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current evidence on endogenous pain modulatory pathways that are activated by repeated massage for painful stimuli suggests that the analgesic effects of massage need to be studied using animal models (Uvnas-Moberg et al, 1993;Lund, 2000;Lund et al, 2002). The majority of recent trials on massage for labour and other forms of pain have been designed to test the effects of structured programmes of massage used in combination with other techniques (Field et al, 1997;Chang et al, 2002;Yildirim and Sahin, 2004;Ezzo, 2007). To improve the quality of evidence on massage interventions combined with relaxation techniques for labour and birth pain, our key task is to follow recent recommendations, to correct design flaws and methodological weakness in existing trials (Smith et al, 2006;Ezzo, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Four trials have been conducted on massage in labour (Field et al, 1997;Chang et al, 2002;Yildirim and Sahin, 2004;Khodakarami et al, 2006). The first involved 28 women randomly assigned to coaching in relaxation breathing techniques alone, or with massage, in a US hospital (Field et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in this regard conducted by Yildirim & Sahin examined the effect of breathing and skin stimulation techniques on labor pain perception among 40 Turkish women. They showed that both breathing and skin stimulation techniques were effective in reducing the perception of pain by pregnant women, which led to a more satisfactory experience of childbirth [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, relieving post caesarean pain is an issue that cannot be ignored. Non-pharmacological methods increased the individual control feeling, decreased the feeling of weakness, improved the activity level and functional capacity, and reduced the needed dosage of analgesic drugs thus decreasing the side effects of the treatment (4) . In recent years, many complementary therapies such as herbal medicines and aromatherapy are tried to help manage pain (5) .…”
Section: Introductionmentioning
confidence: 99%